Well-being and economic conditions in Ireland - Brendan Walsh (University College Dublin, UCD School of Economics, 2011)
By European standards Ireland ranks high on many non-economic indicators of well-being. This paper explores how macroeconomic conditions have affected a range of these indicators. Time series data are used to explore the association between unemployment, inflation, and the level and growth rate of real income on the one hand and measures of subjective well-being and markers of mental health on the other. Over the longer term, 1975-2011, there was no upward trend in self-reported life satisfaction despite the secular improvement in living standards. While higher unemployment reduced life satisfaction over the first half of this period, its effect was weaker in later years. The rate of inflation has not had a significant effect on life satisfaction. There is no evidence that admission rates to psychiatric hospitals are affected by changes in economic conditions. However, higher unemployment is linked to higher suicide rates among younger males, although its effect appears to have weakened during the current recession. Finally, the recent rise in unemployment has had a much smaller impact on the birth rate than that due to the recession of the early 1980s. Overall, the impact of the current recession on the well-being indicators studied here has been surprisingly small.
Keywords: 330; Well-being indicators; Mental health; Suicide; Birth rate; Unemployment; Inflation